KALEMBO ADE AS AN INSTRUMENT OF RESOLVING CONFLICT AMONG MBOJO COMMUNITY: A STUDY ON SPEECH ACT - Sahrain, Muhammad; Irawan, Lalu Ari (IKIP Mataram, 2018)
This study aims at describing variation of meaning carried in kalembo ade as an instrument of resolving conflict among individuals and groups in Mbojo community by applying speech act analysis. Data were collected from speech events in Mbojo community and further analyzed descriptively. One type of speech acts was taken by considering its relevancy towards to focus of this study, i.e. expressive. Results showed that kalembo ade dealt with one of types of speech acts, i.e. Expressive type. The expression was found to reflect some actions, including condolences, apologies, greetings, thanksgivings, refusal, and congratulations. Hence, by viewing the context of usage, members of Mbojo community used this expression as an instrument in communication to resolve conflict, in which the phrase was used as tool to control verbal interaction during a speech event.